ANALISIS EFEKTIVITAS PEMBELAJARAN SOSIOLOGI PADA SISWA KELAS X DI MADRASAH ALIYAH AL-ANWAR PONTIANAK - Pransetyapri, Sholikha Esa; Salim, Izhar; Supriadi, Supriadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis thesis is descriptive in qualitative form. The purpose of this study was to determine the effectiveness of sociology learning in class X students in terms of the quality of learning, of suitability of learning level, of incentives, and of time. Data collection techniques in this study are through interview techniques, observation and documentation. Data collection tools in this study are through documents and archives. Data sources in this study are primary data sources, namely through informants in the study, namely teachers, students and madrasah and secondary supervisors through data reduction, data display and drawing conclusions and verification. Learning effectiveness is said to be effective if students are able to master sociology subjects.. The results of the study show that the effectiveness of sociology learning by teachers in class X is still less effective and needs improvement. The effectiveness of sociology learning in class X is still ineffective, this is due to the lack of facilities and infrastructure provided by madrasas in the learning process as well as the lack of continuous interaction between students and teachers in the sociology learning process which causes less effective sociology learning for class X students at Madrasah Aliyah Al-Anwar Pontianak.Â Keywords:Â  Effectiveness, Sociology Learning.